1999
DOI: 10.1093/jnci/91.12.1067
|View full text |Cite
|
Sign up to set email alerts
|

Urinary 2-Hydroxyestrone/16 -Hydroxyestrone Ratio and Risk of Breast Cancer in Postmenopausal Women

Abstract: This study does not support the hypothesis that the ratio of the two hydroxylated metabolites (2-OHE1/16alpha-OHE1) is an important risk factor for breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(57 citation statements)
references
References 48 publications
2
54
0
1
Order By: Relevance
“…Most but not all case-control studies investigating the role of estrogen metabolism in postmenopausal breast cancer risk support the hypothesis that greater 2-OHE1 levels protect against breast cancer while greater 16a-OHE1 may increase risk. [26][27][28][29][30][31] Differences in these findings may be an artifact of study design, including small sample sizes (usually less than 50 cases), noncomparable controls and the use of spot urine samples to measure metabolite levels, which may be sensitive to changes in excretory patterns and function. Moreover, the presence of the tumor or an endocrine response to treatment, both of which may be present in women recruited after diagnosis, may alter metabolite levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most but not all case-control studies investigating the role of estrogen metabolism in postmenopausal breast cancer risk support the hypothesis that greater 2-OHE1 levels protect against breast cancer while greater 16a-OHE1 may increase risk. [26][27][28][29][30][31] Differences in these findings may be an artifact of study design, including small sample sizes (usually less than 50 cases), noncomparable controls and the use of spot urine samples to measure metabolite levels, which may be sensitive to changes in excretory patterns and function. Moreover, the presence of the tumor or an endocrine response to treatment, both of which may be present in women recruited after diagnosis, may alter metabolite levels.…”
Section: Discussionmentioning
confidence: 99%
“…16a-OHE1 retains potent hormonal activities by binding strongly to the estrogen receptor. 22 Laboratory data [23][24][25] and some but not all epidemiologic studies [26][27][28][29][30][31][32][33][34] suggest a positive association between 16a-OHE1 levels and breast cancer risk. In contrast, 2-OHE1 binds to the estrogen receptor with reduced affinity 35 and because of O-methylation is cleared rapidly from circulation.…”
mentioning
confidence: 99%
“…However, the relationship between urinary 2OHE 1 :16OHE 1 ratios and breast cancer risk is not clear. Although women with breast cancer had lower urinary ratios of 2OHE 1 :16αOHE 1 in several small case-control studies [35][36][37], larger case-control and prospective cohort studies have not found significant associations between urinary 2OHE 1 :16αOHE 1 ratios and breast cancer risk [38][39][40].…”
Section: Effects Of Indole-3-carbinol On Estrogen Metabolismmentioning
confidence: 99%
“…Our study also showed that 2(OH)-E and 16a(OH)-E 1 were stable enough to be measured in urine samples stored at )20°C for more 25 years without any added preserving agents. Absolute values in the frozen samples were not different from those in fresh urine samples from post-menopausal women (average data within ''normal'' post-menopausal range on fresh urine samples were provided by the kit manufacturer), or in urine samples that were stored for much shorter periods of time, measured with the same method [8,[24][25][26]. The apparent stability of hormones during storage time, even at a temperature of )20°C, may be an important issue for prospective epidemiological studies in which biological samples are stored frozen over many years.…”
Section: Discussionmentioning
confidence: 99%